2020
DOI: 10.1002/agj2.20191
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of rolling, mineral oil, sulfur, and phosphorous acid affect Microdochium patch severity

Abstract: Microdochium patch is a turfgrass disease that occurs in cool, humid regions caused by the fungal pathogen Microdochium nivale (Fr.) Samuels & Hallett [Teleomorph = Monographella nivalis (Schaffnit) E. Müll]. Fungicide applications are the predominant method of control; however, pesticide restrictions have generated concern regarding the use of traditional chemicals to manage turfgrass pests. The objective of this research was to evaluate the effects of the cultural practice of rolling in combination with appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…19.9 kg MO ha −1 + 3.7 kg H 3 PO 3 ha A previous study demonstrated that applications of 19.9 kg of mineral oil ha −1 either alone or in a tank mix with 3.7 kg H 3 PO 3 ha −1 and/or with 12.2 kg S ha −1 every 2 wk suppressed Microdochium patch compared to a non-treated control, although severe turfgrass thinning was observed (Mattox et al, 2020). Other research in Scandinavia found the use of 19.9 or 39.8 kg ha −1 of mineral oil applied as a tank mix with 3 kg H 3 PO 3 ha −1 every 3 wk resulted in a 94 and 98% Microdochium patch suppression compared to a non-treated control, respectively (Aamlid et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…19.9 kg MO ha −1 + 3.7 kg H 3 PO 3 ha A previous study demonstrated that applications of 19.9 kg of mineral oil ha −1 either alone or in a tank mix with 3.7 kg H 3 PO 3 ha −1 and/or with 12.2 kg S ha −1 every 2 wk suppressed Microdochium patch compared to a non-treated control, although severe turfgrass thinning was observed (Mattox et al, 2020). Other research in Scandinavia found the use of 19.9 or 39.8 kg ha −1 of mineral oil applied as a tank mix with 3 kg H 3 PO 3 ha −1 every 3 wk resulted in a 94 and 98% Microdochium patch suppression compared to a non-treated control, respectively (Aamlid et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…shown excellent suppression of Microdochium patch following repeated preventative applications of phosphite products (Dempsey et al, 2018;Mattox, Kowalewski, McDonald, Lambrinos, et al, 2020). Phosphite products have also demonstrated various levels of efficacy against other turfgrass diseases such as Pythium blight (Pythium aphanidermatum) and anthracnose (Colletotrichum cereale), but not typically to commercially acceptable levels without support from traditional fungicides (Burpee, 2005;Cook et al, 2009).…”
Section: Core Ideasmentioning
confidence: 99%
“…pressed Microdochium patch although unacceptable turfgrass thinning occurred (Mattox et al, 2020). This manuscript focuses on two different field experiments that quantify Microdochium patch suppression and turfgrass quality.…”
Section: Core Ideasmentioning
confidence: 99%
“…Alternatives to traditional fungicides that have been shown to suppress Microdochium patch include mineral oil on creeping bentgrass ( Agrostis stolonifera L.) (Cortes‐Barco et al., 2010a), S on colonial bentgrass ( A. capillaris L.) (Brauen et al., 1975), and phosphorous acid (H 3 PO 3 ) on both annual bluegrass and velvet bentgrass ( A. canina L.) (Dempsey et al., 2012). A tank mixture of S and H 3 PO 3 has been shown to suppress Microdochium patch more than when either S or H 3 PO 3 were applied alone (Mattox et al., 2020). A few mineral oils and S products are registered for organic agriculture (OMRI, 2020) and these may be permitted in some places where traditional fungicides are not allowed (South Portland, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation